Metabolic pathways fueling the suppressive activity of myeloid-derived suppressor cells - Goldmann, Oliver; Medina, Eva (Frontiers in Immunology, 2024)
Myeloid-derived suppressor cells (MDSC) are considered an aberrant population of immature myeloid cells that have attracted considerable attention in recent years due to their potent immunosuppressive activity. These cells are typically absent or present in very low numbers in healthy individuals but become abundant under pathological conditions such as chronic infection, chronic inflammation and cancer. The immunosuppressive activity of MDSC helps to control excessive immune responses that might otherwise lead to tissue damage. This same immunosuppressive activity can be detrimental, particularly in cancer and chronic infection. In the cancer setting, tumors can secrete factors that promote the expansion and recruitment of MDSC, thereby creating a local environment that favors tumor progression by inhibiting the effective immune responses against cancer cells. This has made MDSC a target of interest in cancer therapy, with researchers exploring strategies to inhibit their function or reduce their numbers to improve the efficacy of cancer immunotherapies. In the context of chronic infections, MDSC can lead to persistent infections by suppressing protective immune responses thereby preventing the clearance of pathogens. Therefore, targeting MDSC may provide a novel approach to improve pathogen clearance during chronic infections. Ongoing research on MDSC aims to elucidate the exact processes behind their expansion, recruitment, activation and suppressive mechanisms. In this context, it is becoming increasingly clear that the metabolism of MDSC is closely linked to their immunosuppressive function. For example, MDSC exhibit high rates of glycolysis, which not only provides energy but also generates metabolites that facilitate their immunosuppressive activity. In addition, fatty acid metabolic pathways, such as fatty acid oxidation (FAO), have been implicated in the regulation of MDSC suppressive activity. Furthermore, amino acid metabolism, particularly arginine metabolism mediated by enzymes such as arginase-1, plays a critical role in MDSC-mediated immunosuppression. In this review, we discuss the metabolic signature of MDSC and highlight the therapeutic implications of targeting MDSC metabolism as a novel approach to modulate their immunosuppressive functions.